Some New Inequalities Using Nonintegral Notion of Variables - Abha Singh; Abdul Hamid Ganie; Mashael M. Albaidani (Advances in Mathematical Physics)
The object of this paper is to present an extension of the classical Hadamard fractional integral. We will establish some new results of generalized fractional inequalities.